Electroless Metallization of Stereolithographic Photocurable Resins for 3D Printing. (28th July 2016) - Bernasconi, Roberto; Credi, Caterina; Natale, Gabriele; Tironi, Marco; Cuneo, Federico; Levi, Marinella; Magagnin, Luca
Abstract : In the present paper the electroless metallization of 3D printed parts using stereolithography is investigated. Two different photocurable resins of large commercial diffusion and a self-formulated one are used as starting materials for printing. A first metal layer of NiP or Cu, obtained by an optimized pretreatment and plating process, is subsequently applied on the parts. It is also demonstrated the possibility of obtaining multilayers through the successive electrodeposition of different metals on the electroless treated parts. The resulting layers are characterized by SEM and profilometry.